Feasibility of Transcatheter Closure of Large Secundum Atrial Septal Defect with Absent Superior or Inferior Rim - Hussein Abdulwahab; Mohammed Rassul Husain; Khalid A. Khalid (Journal of Interventional Cardiology)
Introduction. Surgical closure of a large secundum atrial septal defect (ASD) with an absent superior or inferior rim is the standard method of management, but transcatheter closure of such a defect is possible and feasible. Objectives. To evaluate the feasibility, effectiveness, and safety of transcatheter closure of large secundum ASD with an absent superior or inferior rim through implantation of a cheatham platinum (CP) stent at the entrance of the superior vena cava (SVC) or inferior vena cava (IVC) into the right atrium (RA) to create a suitable rim for subsequent complete closure of the defect using a septal occluder. Patients and Methods. This case series was carried out at Ibn Al-Bitar Center for Cardiac Surgery, Baghdad, Iraq from 2014 to 2019, five patients underwent such transcatheter approach for closure of large secundum ASD with the absent superior or inferior rim by implantation of CP stent at the entrance of vena cave into the RA. Result. The ages and weights of patients who were enrolled in this study ranged from 9–31 years (15.2 ± 9 years) and 31.5–62 kg (42.6 ± 12 kg). Three patients had absent superior rims, and the other two had absent inferior rims. The Qp/Qs was ranged from 1.9–3.2 (2.78 ± 0.29), and the mean pulmonary arterial pressure ranged from 22–29 mmHg (25.4 ± 3 mmHg). The defects with an absent superior rim were closed successfully by implantation of CP stents of 45, 45, and 39 mm to create a rim which supported the left atrial disc of 30, 38, and 32 mm atrial septal occluder (ASO), respectively, while large secundum ASD with an absent inferior rim could be effectively closed by implantation of two overlapping bare CP stents of 45 mm to create an IVC rim that supported 34 mm and 30 mm atrial septal occluder. Conclusion and recommendation. Transcatheter closure of large secundum ASD with absent superior or inferior rim is possible and effective by implantation of covered and bare CP stents at the entrance of SVC and IVC, respectively. Although these procedures are relatively difficult and challenging, especially in the closure of large defects associated with absent inferior rim, they carry a high risk of stent migration (8 zig, 45 mm), so we recommend using a CP-stent (10 zig, 60 mm).